Maqashid Shariah's Criticism of the Pareto Optimum Theory - Iwan Setiawan (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
AbstractThis research analyzes the concept of maqashid sharia and the optimum Pareto theory. It was conducted in the form of library research, where data was obtained from literatures relating to the development of Islamic economics, the optimum Pareto theory, and maqashid sharia. Qualitative techniques were used to analyze unquantifiable data. The results show that the optimum Pareto theory has weaknesses and does not guarantee justice for the whole community. For instance, in achieving maximum efficiency, others must be sacrificed. This is contrary to the concept of Islamic economics which emphasizes justice for all parties to a transaction. Maqashid sharia has values that guide religion (din), soul (nafs), reasoning ('aql), property (mall), and offspring (nasab) as a reference to explain the weakness of the Pareto optimum theory. It applies especially in the distribution of wealth and welfare of the people. Pareto efficiency cannot be used as a basis for achieving economic goals since it is not impartial.